DEVELOPMENT OF E-LKPD BASED ON PROBLEM BASED LEARNING (PBL) ON SEQUENCES AND SERIES FOR GRADE X: Padang, Indonesia - Resi Arti Nanda; Radhya Yusri; Anna Cesaria (Universitas Muhammadiyah Bengkulu, 2025)
This study was conducted in response to the fact that the teaching materials used in mathematics instruction at SMA Negeri 1 Sitiung have not yet fully addressed students’ learning needs. The objective of this research is to develop a valid E-LKPD (Electronic Student Worksheet) based on Problem-Based Learning (PBL) for the topic of sequences and series in grade X. This study employs a Research and Development (R&D) approach, utilizing the Plomp development model. The validation results of the PBL-based E-LKPD obtained a score of 89.8%, categorized as very valid. These findings indicate that the PBL-based E-LKPD for the sequences and series material in grade X at SMA Negeri 1 Sitiung is valid and suitable for use by both teachers and students during the learning process. Keywords: E-LKPD, Problem Based Learning, Sequences and Series